Single-step electrochemical deposition of antimicrobial orthopaedic coatings based on a bioactive glass/chitosan/nano-silver composite system - Pishbin, F. (2013)
Composite orthopaedic coatings with antibacterial capability containing chitosan, Bioglass® particles (9.8ìm) and silver nanoparticles (Ag-np) were fabricated using a single-step electrophoretic deposition (EPD) technique, and their structural and preliminary in vitro bactericidal and cellular properties were investigated. Stainless steel 316 was used as a standard metallic orthopaedic substrate. The coatings were compared with EPD coatings of chitosan and chitosan/Bioglass®. The ability of chitosan as both a complexing and stabilizing agent was utilized to form uniformly deposited Ag-np. Due to the presence of Bioglass® particles, the coatings were bioactive in terms of forming carbonated hydroxyapatite in simulated body fluid (SBF). Less than 7wt.% of the incorporated silver was released over the course of 28days in SBF and the possibility of manipulating the release rate by varying the deposition order of coating layers was shown. The low released concentration of Ag ions (<2.5ppm) was efficiently antibacterial against Staphyloccocus aureus up to 10days. Although chitosan and chitosan/Bioglass® coating supported proliferation of MG-63 osteoblast-like cells up to 7days of culture, chitosan/Bioglass®/Ag-np coatings containing 342 ìg of Ag-np showed cytotoxic effects. This was attributed to the relatively high concentration of Ag-np incorporated in the coatings.